Selenoprotein P Promotes the Development of Pulmonary Arterial Hypertension: Possible Novel Therapeutic Target. Issue 6 (7th August 2018) - Kikuchi, Nobuhiro; Satoh, Kimio; Kurosawa, Ryo; Yaoita, Nobuhiro; Elias-Al-Mamun, Md.; Siddique, Mohammad Abdul Hai; Omura, Junichi; Satoh, Taijyu; Nogi, Masamichi; Sunamura, Shinichiro; Miyata, Satoshi; Saito, Yoshiro; et al.
Abstract : Background: Excessive proliferation and apoptosis resistance of pulmonary artery smooth muscle cells (PASMCs) are key mechanisms of pulmonary arterial hypertension (PAH). Despite the multiple combination therapy, a considerable number of patients develop severe pulmonary hypertension (PH) because of the lack of diagnostic biomarker and antiproliferative therapies for PASMCs. Methods: Microarray analyses were used to identify a novel therapeutic target for PAH. In vitro experiments, including lung and serum samples from patients with PAH, cultured PAH-PASMCs, and high-throughput screening of 3336 low-molecular-weight compounds, were used for mechanistic study and exploring a novel therapeutic agent. Five genetically modified mouse strains, including PASMC-specific selenoprotein P (SeP) knockout mice and PH model rats, were used to study the role of SeP and therapeutic capacity of the compounds for the development of PH in vivo. Results: Microarray analysis revealed a 32-fold increase in SeP in PAH-PASMCs compared with control PASMCs. SeP is a widely expressed extracellular protein maintaining cellular metabolism. Immunoreactivity of SeP was enhanced in the thickened media of pulmonary arteries in PAH. Serum SeP levels were also elevated in patients with PH compared with controls, and high serum SeP predicted poor outcome. SeP-knockout mice ( SeP –/– ) exposed to chronic hypoxia showed significantly reduced right ventricular systolic pressure, right ventricular hypertrophy, and pulmonary artery remodeling compared with controls. In contrast, systemic SeP-overexpressing mice showed exacerbation of hypoxia-induced PH. Furthermore, PASMC-specific SeP –/– mice showed reduced hypoxia-induced PH compared with controls, whereas neither liver-specific SeP knockout nor liver-specific SeP-overexpressing mice showed significant differences with controls. Altogether, protein levels of SeP in the lungs were associated with the development of PH. Mechanistic experiments demonstrated that SeP promotes PASMC proliferation and resistance to apoptosis through increased oxidative stress and mitochondrial dysfunction, which were associated with activated hypoxia-inducible factor-1α and dysregulated glutathione metabolism. It is important to note that the high-throughput screening of 3336 compounds identified that sanguinarine, a plant alkaloid with antiproliferative effects, reduced SeP expression and proliferation in PASMCs and ameliorated PH in mice and rats. Conclusions: These results indicate that SeP promotes the development of PH, suggesting that it is a novel biomarker and therapeutic target of the disorder. Abstract : Supplemental Digital Content is available in the text.